PENINGKATAN KETERAMPILAN MENULIS KARANGAN DESKRIPTIF MELALUI PEMBELAJARAN DENGAN MENGGUNAKAN MEDIA POP UP PADA SISWA SEKOLAH DASAR - Lestari, Renanda Yuliana; Sumianto, Sumianto; Ananda, Rizki (Jurnal Muassis Pendidikan Dasar, 2023)
The research is motivated by the low writing skills of the fifth grade studens of SDN 024 Limau Manis. One solution to overcome this problem is to use Pop Up media. This study aims to describe the application of  Pop Up media to improve studens’ descriptive essay writing skills in thematic learning of indonesian languange content. This reseach method is classroom action reseach (PTK) which is carried out in two cycles. Each cycle consists of two mwwtings and four stages, namely planning, implementation, observation, reflection. The subject of this research of SDN 024 Limau Manis for the academic year 2021/2022, totaling 9 students. Data collection teachniques used in this study were observation, test, and documentation techniques. Based on the results of the researchers, it can be concluded that Pop Up media can improve students’ descriptive essay writing skills in thematic learning content in the thematic learning content of Indonesian languange students at SDN 024 Limau Manis, improve students’ descriptive essay writing skills, that is, from an average of 70,5% in cycle I, and increased to 80,5% with good criteria in cycle II.  Thus it can be concluded that using Pop Up media can improve students’ descriptive essay writing skills in thematic learning of Indonesian languange content in fifth grade students of SDN 024 Limau Manis.